KALAHARI GROUP FINALIST IN MEA 2016 BEST STUDENT ENTERPRISE AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
KUALA LUMPUR, 27 January 2017 A Universiti Sains Malaysia (USM) student from its School of Health Sciences, Mohamad Nazri Mohd Anowar has made the university proud after being chosen as one of the finalists for the Best Student Enterprise Award at the MOHE Entrepreneurial Awards (MEA) 2016.